Sosialisasi Penggunaan Media Pop Up Book di SD Negeri Malaka - Yufrizal Yufrizal; Patri Janson Silaban; Lasma Silaban (Universitas 45 Surabaya, 2024)
This service or socialization was motivated by a problem among students at SD Negeri Malaka Class II, namely that many students were still not fluent in reading. This happens because teachers are lacking in implementing literacy movements such as reading 15 minutes before studying, not implementing reading corners in the classroom and not using media and models appropriately, teachers are not playing an active role in inviting students to visit the school library and teachers are not providing assistance to students. in supervising learning, especially Indonesian language learning, namely in the aspect of reading skills, namely reading poetry, therefore it is seen that students lack enthusiasm in learning. The teacher must choose the right model and use interesting, creative and innovative learning media. Therefore, the teacher takes steps by using pop up book media to increase students' reading interest. The approach or method used is Participatory Action Research (PAR) which is a research approach that involves active participation from community groups who are research subjects. This method aims to produce knowledge that is relevant, useful and can be applied in everyday life. This activity was carried out at Malaka Class II Elementary School. With the presence of Pop up book media, students will be inspired and increase their interest in reading. by using Media.